2014
DOI: 10.7448/ias.17.4.19661
|View full text |Cite
|
Sign up to set email alerts
|

Should screening for Chlamydia trachomatis and Neisseria gonorrhoeae in HIV‐men who have sex with men be recommended?

Abstract: IntroductionSexually transmitted infections (STI) like Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) have been associated with increased risk of HIV acquisition [1]. It has been also described as a high prevalence of asymptomatic CT and NG infections in men who have sex with men (MSM) [2]. The aim of this study was to know the prevalence of CT and/or NG infections in asymptomatic HIV-MSM and the related factors.Materials and MethodsProspective study of a cohort of asymptomatic HIV-MSM with follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Our study also suggested that more than half of respondents believed that routine CT screening was the most appropriate to undertake CT test and most of them were willing to undertake routine CT screening. A previous study found that CT screening had great acceptance in this population ( 26 ). However, a third of participants were willing to undertake routine CT screening if the test is free, which suggested that offering free CT tests could expand the uptake of screening.…”
Section: Discussionmentioning
confidence: 89%
“…Our study also suggested that more than half of respondents believed that routine CT screening was the most appropriate to undertake CT test and most of them were willing to undertake routine CT screening. A previous study found that CT screening had great acceptance in this population ( 26 ). However, a third of participants were willing to undertake routine CT screening if the test is free, which suggested that offering free CT tests could expand the uptake of screening.…”
Section: Discussionmentioning
confidence: 89%
“…The findings are also in line with previous studies that demonstrated the association between HIV infection and higher incidence and prevalence rates of other STIs, supporting linked epidemics of STIs and HIV in Portuguese MSM. [26][27][28] Interventions for MSM should combine HIV-testing and STI-testing, and for some of the clusters identified in our analysis, should be comprehensive, including rectal and pharyngeal swabbing to screen for asymptomatic gonorrhoea and chlamydia, especially considering the current challenges with antimicrobial resistance. 29 It should be mentioned that, the information on the natural history of these asymptomatic infections is scarce, and the public health benefit and the risks associated with the wide roll-out of this screening strategy remain unclear.…”
Section: Discussionmentioning
confidence: 99%